A High‐Sensitivity 10‐Color Flow Cytometric Minimal Residual Disease Assay in B‐Lymphoblastic Leukemia/Lymphoma Can Easily Achieve the Sensitivity of 2‐in‐106 and Is Superior to Standard Minimal Residual Disease Assay: A Study of 622 Patients. Issue 1 (14th June 2019) - Tembhare, Prashant R.; Subramanian PG, Papagudi G.; Ghogale, Sitaram; Chatterjee, Gaurav; Patkar, Nikhil V.; Gupta, Avinash; Shukla, Rahul; Badrinath, Yajamanam; Deshpande, Nilesh; Narula, Gaurav; Rodrigues, Pearl; Girase, Karishma; et al.
Abstract : Background: Flow‐cytometric minimal residual disease (FC‐MRD) monitoring is a well‐established risk‐stratification factor in B‐lymphoblastic leukemia/lymphoma (‐B‐ALL) and is being considered as a basis for deintensification or escalation in treatment protocols. However, currently practiced standard FC‐MRD has limited sensitivity (up to 0.01%) and higher false MRD‐negative rate. Hence, a highly sensitive, widely applicable, and easily reproducible FC‐MRD assay is needed, which can provide a reliable basis for therapeutic modifications. Methods: A 10‐color high‐event analysis FC‐MRD assay was studied for the evaluation of MRD status at postinduction, (PI; day‐35), postconsolidation, (PC; day‐78), and subsequent follow‐up time‐points (SFU) in bone marrow samples from pediatric B‐ALL. Results: One‐thousand MRD samples (PI‐62.2%; PC‐26.5%; and SFU‐11.3%) from 622 childhood B‐ALL patients were studied. High‐event analysis was performed with median 4, 452, 000 events (range, 839, 000 to 8, 866, 000 events) and >4 million events in 71% samples. MRD was measurable in 43.2% of PI‐samples, in 29.4% PC‐samples, and in 32.7% SFU‐samples. To simulate comparison with standard FC‐MRD, we reanalyzed MRD results gating only first 500, 000 and first 1000, 000 events in 122 PI‐MRD positive samples with MRD levels <0.02%. Of these samples gated for 500, 000 events and 1000, 000 events, 32% and 21.3% were found to be falsely MRD‐negative, respectively. Conclusions: We report an easily reproducible high‐sensitivity 10‐color FC‐MRD assay with the sensitivity of 2‐in‐10 6 (0.0002%). It allowed the detection of low‐level MRD in samples, which could have been reported negative using the standard FC‐MRD with limited event analysis. Thus, this high‐sensitivity MRD‐methodology can provide a reliable basis for therapeutic modifications in B‐ALL. © 2019 International Clinical Cytometry Society